MODELAGEM MATEMÁTICA DO ACIONAMENTO HIDRÁULICO DE UMA BANCADA DE ENSAIO DE PÓRTICOS - Fracaro, Adonis R.; Valdiero, Antonio C.; Gonçalves, Marcia F.; Rasia, Luiz A. (Salão do Conhecimento, 2013)
Resumo